Pemodelan dan Estimasi Sumberdaya Bijih Emas di PT. DEF Kecamatan Simpenan, Kabupaten Sukabumi, Provinsi Jawa Barat - Muhamad Kaisya Hidayat; Noor Fauzi Isniarno; Zaenal (Bandung Conference Series: Mining Engineering, 2022)
Abstract. PT. DEF has a gold and silver mining concession located in Sukabumi district, West Java. Several open pit mining and conventional processing support the production of gold and silver bullion. The mining operations which started in 1995 have shaped the company's reputation as an industry in terms of safety, sustainability and operational performance. PT. DEF prioritizes environmental conservation and the interests of the community as an integral part of its mining cycle. To find out the gold potential of the company, exploration activities are needed which can then be carried out geological modeling of gold ore and calculating the amount of mineral resources. Resource modeling is a series of explorations in the mining sector. In this study, modeling of gold (Au) resources aims to identify, determine a geological picture and delineate in detail the size, shape, distribution, quality and quantity of the ore body in 3D obtained from pilot data in exploration activities. The data needed from exploration data to continue in the collection and processing are drill point coordinate data (collar), lithology data, grade (assay/geology), drill hole direction data, dip and azimuth (survey). In the processing and analysis of Au resources and reserves using the Ordinary Kriging estimation method with a model block size of 1x1x1 meters then calculations are carried out based on the Cut Off Grade (COG) value and classification using Kriging Efficiency. The results of data processing and lithological modeling show the distribution of tuff, breccia and andesite alteration, which tends to lead to the surface in the form of an outcrop. The results of data processing, resource estimates that have been carried out in the research area are divided into two blocks. Block A has a total volume of 243,373 BCM with a tonnage value of 511,083 tons with an inferred resource classification resulting in a volume of 185,849 BCM with a tonnage value of 390,282,9 tons, an indicated volume of 36,949 BCM with a tonnage value of 77,592,9 tons, a measured resource classification the resulting volume is 20,575 BCM with a tonnage value of 43,207.5 tons. Block B has a total volume of 133,460 BCM with a tonnage value of 280,266 tons with an inferred resource classification resulting in a volume of 75,159 BCM with a tonnage value of 157,833.9 tons, indicated a volume of 32,364 BCM with a tonnage value of 67,964.4 tons, a measured resource classification the resulting volume is 25,937 BCM with a tonnage value of 54,467.7 tons. Abstrak. PT. DEF memiliki konsensi pertambangan emas dan perak terletak di kabupaten Sukabumi, Jawa Barat. Beberapa pit tambang terbuka dan pengolahan konvensional mendukung produksi emas dan perak batangan. Operasi tambang yang telah dimulai pada tahun 1995 telah membentuk reputasi perusahaan sebagai industri dalam hal keselamatan, keberlanjutan dan kinerja operasional. PT. DEF mengutamakan pelestarian lingkungan dan kepentingan masyarakat sebagai bagian integral dalam siklus penambangannya.Untuk mengetahui potensi emas pada perushaan tersebut diperlukannya kegiatan eksplorasi yang kemudian dapat dilakukannya pemodelan geologi bijih emas dan menghitung jumlah sumberdaya bahan galiannya. Pemodelan sumberdaya merupakan suatu rangkaian eksplorasi dalam bidang pertambangan. Pada penelitian ini, pemodelan sumberdaya emas (Au), bertujuan untuk mengidentifikasi, menentukan suatu gambaran geologi dan mendeliniasi secara rinci mengenai ukuran, bentuk, sebaran, kualitas dan kuantitas badan bijih dalam bentuk 3D yang didapatkan dari data-data percontohan dalam kegiatan eksplorasi. Data-data yang diperlukan dari data eksplorasi untuk melanjutkan dalam pengimputan dan pengolahan adalah data koordinat titik bor (collar),data litologi, kadar (assay), data arah lubang bor, dip dan azimuth (data bor). Dalam pengolahan dan analiasa sumberdaya dan cadangan Au menggunakan metode estimasi Ordinary Kriging dengan ukuran blok model yaitu 1x1x1 meter kemudian dilakukan perhitungan berdasarkan nilai Cut Off Grade (COG) serta pengklasifikasian menggunakan Kriging Efisiensi. Hasil Pengolahan data dan pemodelan litologi menunjukan sebaran tufa, breksi dan alterasi andesit, yang kecenderungan batuannya mengarah ke permukaan berupa suatu singkapan. Hasil Pengolahan data, estimasi sumberdaya yang telah dilakukan pada daerah penelitian yaitu dibagi kedalam dua blok. Blok A mendapatkan volume total sebanyak 243.373 BCM dengan nilai tonnase sebesar 511.083 ton dengan klasifikasi sumberdaya tereka dihasilkan volume sebesar 185.849 BCM dengan nilai tonnase sebesar 390.282,9 ton, tertunjuk dihasilkan volume sebesar 36.949 BCM dengan nilai tonnase sebesar 77.592,9 ton, klasifikasi sumberdaya terukur dihasilkan volume sebesar 20.575 BCM dengan nilai tonnase sebesar 43.207,5 ton. Blok B mendapatkan volume total sebanyak 133.460 BCM dengan nilai tonnase sebesar 280.266 ton dengan klasifikasi sumberdaya tereka dihasilkan volume sebesar 75.159 BCM dengan nilai tonnase sebesar 157.833,9 ton, tertunjuk dihasilkan volume sebesar 32.364 BCM dengan nilai tonnase sebesar 67.964,4 ton, klasifikasi sumberdaya terukur dihasilkan volume sebesar 25.937 BCM dengan nilai tonnase sebesar 54.467,7 ton.